Determination of Shallow Ground Water Quality and Management Guidelines (Case Study at Sumenep) - Widiatmono, J. Bambang Rahadi; Lusiana, Novia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Population growth in urban areas Sumenep consequences of the impact of increased demand for residential land. Fulfillment of the general water supply comes from surface water and groundwater. In recent years, there are indications of decline in the quality of underground water is characterized by an increased disease caused by water (water borne disease), so it is necessary to study the quality of underground water. The purpose of this study is to identify water quality, analysis, evaluation, and formulate the direction of ground water quality management. Methods of water analysis is done by comparing the results of observations of water quality parameters of class 1 (raw water). Location of the observations were made in three areas Golden Stone, Satellites and Underpants. The results demonstrate for the number of parameters that exceeded water quality class 1 (raw water) include parameters of iron (Fe), Copper (Cu) and Total Phosphate and it can be concluded that the quality of water in the water Sumenep classified in Class B (good) polluted with mild level, so it’s worth drinking water as a raw material but still need processing (cooking) in advance. Keywords: management guidelines, quality standards, water quality